2014
DOI: 10.1111/jpim.12226
|View full text |Cite
|
Sign up to set email alerts
|

Who Knows What inNPDTeams: Communication Context, Mode, and Task Contingencies

Abstract: The use of cross‐functional teams in new product development (NPD) benefits firms in many ways. One benefit is the diverse knowledge team members bring to the project, but that benefit can only be appreciated if team members fully utilize and integrate the differentiated expertise of members. As reliance on cross‐functional NPD teams grows, however, firms struggle to exploit the full potential of functionally diverse groups, the biggest obstacle being integrating team members' varied knowledge, expertise, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 101 publications
1
36
0
Order By: Relevance
“…Scholars have also examined the influence of communication contexts and modes on TMS. In new product development teams, task exploration and task exploitation moderated the positive association between four communication types (i.e., informal-, formal-, face-to-face-, and computer-mediated communication) and TMS (Tang, Mu, & Thomas, 2014). Tang et al defined task exploration as searching for and experimenting to find new knowledge, and task exploitation as capitalizing on existing knowledge.…”
Section: Communication Medium and Group Developmentmentioning
confidence: 99%
“…Scholars have also examined the influence of communication contexts and modes on TMS. In new product development teams, task exploration and task exploitation moderated the positive association between four communication types (i.e., informal-, formal-, face-to-face-, and computer-mediated communication) and TMS (Tang, Mu, & Thomas, 2014). Tang et al defined task exploration as searching for and experimenting to find new knowledge, and task exploitation as capitalizing on existing knowledge.…”
Section: Communication Medium and Group Developmentmentioning
confidence: 99%
“…As a result, Salomo et al () see global innovation teams, which are highly diverse in the geographic location of their members, as representing an important antecedent to global innovation success. Complementing these results, Tang et al () found that developing a transactive memory system (TMS) in teams consisting of members from diverse geographic locations facilitates the team’s innovation performance. In this respect, Tang et al () stress the importance of communication within these teams and point to the key role of selecting the appropriate communication context and mode in which to develop TMS.…”
Section: The Role Of Team Diversity In Innovationmentioning
confidence: 94%
“…This is also a surface‐level attribute of job‐unrelated diversity. Both the selected studies in this domain use cross‐sectional field surveys to investigate this type of team diversity with one basing on a key respondent design (Salomo et al, ) and the other on a multi‐informant design ( Tang et al, ). The selected studies on diversity in geographic location use the resource‐based view of the firm (Salomo et al, ) and the knowledge‐based view of the firm (Tang et al, ) as their theoretical foundations.…”
Section: The Role Of Team Diversity In Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…These organizational performance measures have been frequently used in previous literature (Tang et al, 2015).…”
Section: Measurement and Validation Of Constructsmentioning
confidence: 99%